2014
DOI: 10.1177/1087054714542001
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems and Daily Functioning in Children With ADHD: An Investigation of the Role of Impairment, ADHD Presentations, and Psychiatric Comorbidity

Abstract: Sleep problems and impaired daily functioning were more common in children with ADHD, but the overall association between sleep problems and impaired daily functioning was similar in clinical and nonclinical children. Internalizing or autistic comorbid disorders added significantly to the sleep problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…A number of findings emerged. First, results from questionnaire‐based measures and a 1‐week parent diary suggested that sleep problems are highly prevalent among children with ADHD and that it takes longer for children with ADHD than control children to fall asleep, which parallels what is reported generally in questionnaire studies of sleep in ADHD (Cortese et al ., ; Virring et al ., ; Yoon et al ., ). When sleep was measured through objective sleep measures, a higher numbers of sleep cycles, less total sleep time, less NREM 1 and NREM 3 sleep and more REM sleep were found in ADHD compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of findings emerged. First, results from questionnaire‐based measures and a 1‐week parent diary suggested that sleep problems are highly prevalent among children with ADHD and that it takes longer for children with ADHD than control children to fall asleep, which parallels what is reported generally in questionnaire studies of sleep in ADHD (Cortese et al ., ; Virring et al ., ; Yoon et al ., ). When sleep was measured through objective sleep measures, a higher numbers of sleep cycles, less total sleep time, less NREM 1 and NREM 3 sleep and more REM sleep were found in ADHD compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies using questionnaire data have investigated the influence of ADHD presentation or psychiatric comorbidity on sleep in ADHD. The few studies that exist conclude that the presence of comorbid psychiatric disorders such as autism spectrum disorders or internalizing disorders seem to influence sleep, whereas the different ADHD presentations do not appear to differ with respect to sleep disturbance (Chiang et al ., ; Hansen et al ., ; LeBourgeois et al ., ; Mayes et al ., ; Virring et al ., ; Wagner et al ., ; Willoughby et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…This is especially important since sleep problems predict functional impairment in youth with ADHD 17,29,31,70,71 . Appreciably, recent interventions have been developed that aim to directly target sleep problems in children with ADHD 72,73 .…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety symptoms may be especially detrimental to the sleep functioning of children with ADHD 14,30 . It is less clear if externalizing behaviors such as oppositionality are associated with sleep functioning in children with ADHD 16,17,3133 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, meta-analytic studies suggest high rates of sleep disturbance occur in both medicated and unmedicated children with ADHD (Cohen-Zion & Alcoli-Israel, 2004). Moreover, while sleep problems and impaired daily functioning are common among children with ADHD, theoverall associations between sleep problems and impaired daily functioning are similar in clinical and nonclinical children (Virring et al, 2014). …”
Section: Introductionmentioning
confidence: 99%